Thermal shock testing of monolithic refractories - Tomba Martinez, Analia Gladys (2009)
A simple technique for evaluating the thermal shock resistance of monolithic refractories at laboratory scale was implemented ad-hoc. The aim of this contribution is to describe the main features of this technique. The tested material is a monolithic refractory commonly used in electric arc furnace roofs of the steelmaking industry. The proposed methodology is based on the air-cooling of cylindrical specimens and the determination of their residual mechanical resistance by diametrical compression tests.